PENGARUH KUALITAS LAYANAN DALAM PENGGUNAAN MOBILE BANKING TERHADAP KEPUASAN NASABAH BANK BNI 46 KANTOR CABANG BANDA ACEH - Yahya Kobat; Zenitha Maulida; Teuku Furqansyah; Yusni Hervy Yusuf; Syarifah Mauli Masyitah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
The purpose of this study was to determine the effect of Service Quality in the Use of Mobile Banking on Customer Satisfaction of Bank BNI 46 Banda Aceh Branch Offices. The number of samples in this study were 267 respondents. Research data was collected through questionnaires and literature studies. The analysis used in this study is simple linear regression analysis, and hypothesis testing is carried out using the t test which aims to partially determine the effect of the independent variable on the dependent variable at the 95% confidence level (α = 0.05). The results of the research based on the partial test (t test) the variable Service Quality has a significant effect on Customer Satisfaction at the BNI 46 Banda Aceh Branch Office as indicated by tcount (0,0673) > ttable (0,119).